#### 6.4.11 4.4

6.4.11.1 [1092] Problem 1
6.4.11.2 [1093] Problem 2
6.4.11.3 [1094] Problem 3
6.4.11.4 [1095] Problem 4
6.4.11.5 [1096] Problem 5

##### 6.4.11.1 [1092] Problem 1

problem number 1092

Problem Chapter 4.4.4.1, from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $a w_x + b w_y = (c \coth (\lambda x) + k \coth (\mu y)) w$

Mathematica

$\left \{\left \{w(x,y)\to \sinh ^{\frac{c}{a \lambda }}(\lambda x) c_1\left (y-\frac{b x}{a}\right ) e^{\frac{k (\log (\tanh (\mu y))+\log (\cosh (\mu y)))}{b \mu }}\right \}\right \}$

Maple

$w \left ( x,y \right ) ={\it \_F1} \left ({\frac{ya-bx}{a}} \right ) \left ({\rm coth} \left (\lambda \,x\right )-1 \right ) ^{-1/2\,{\frac{c}{a\lambda }}} \left ({\rm coth} \left (\lambda \,x\right )+1 \right ) ^{-1/2\,{\frac{c}{a\lambda }}} \left ({\rm coth} \left (\mu \,y\right )-1 \right ) ^{-1/2\,{\frac{k}{b\mu }}} \left ({\rm coth} \left (\mu \,y\right )+1 \right ) ^{-1/2\,{\frac{k}{b\mu }}}$

________________________________________________________________________________________

##### 6.4.11.2 [1093] Problem 2

problem number 1093

Problem Chapter 4.4.4.2, from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $a w_x + b w_y = c \coth (\lambda x +\mu y) w$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (y-\frac{b x}{a}\right ) \exp \left (\frac{c (\log (\tanh (\lambda x+\mu y))+\log (\cosh (\lambda x+\mu y)))}{a \lambda +b \mu }\right )\right \}\right \}$

Maple

$w \left ( x,y \right ) ={\it \_F1} \left ({\frac{ya-bx}{a}} \right ) \left ({\rm coth} \left (\lambda \,x+\mu \,y\right )-1 \right ) ^{-{\frac{c}{2\,a\lambda +2\,b\mu }}} \left ({\rm coth} \left (\lambda \,x+\mu \,y\right )+1 \right ) ^{-{\frac{c}{2\,a\lambda +2\,b\mu }}}$

________________________________________________________________________________________

##### 6.4.11.3 [1094] Problem 3

problem number 1094

Problem Chapter 4.4.4.3, from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $x w_x + y w_y = a x \coth (\lambda x +\mu y) w$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (\frac{y}{x}\right ) \exp \left (\frac{a x (\log (\tanh (\lambda x+\mu y))+\log (\cosh (\lambda x+\mu y)))}{\lambda x+\mu y}\right )\right \}\right \}$

Maple

$w \left ( x,y \right ) ={\it \_F1} \left ({\frac{y}{x}} \right ) \left ({\rm coth} \left (\lambda \,x+\mu \,y\right )-1 \right ) ^{-1/2\,{a \left ({\frac{\mu \,y}{x}}+\lambda \right ) ^{-1}}} \left ({\rm coth} \left (\lambda \,x+\mu \,y\right )+1 \right ) ^{-1/2\,{a \left ({\frac{\mu \,y}{x}}+\lambda \right ) ^{-1}}}$

________________________________________________________________________________________

##### 6.4.11.4 [1095] Problem 4

problem number 1095

Problem Chapter 4.4.4.4, from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $a w_x + b \coth ^n(\lambda x) w_y = (c \coth ^m(\mu x)+s \coth ^k(\beta y)) w$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (y-\frac{b \coth ^{n+1}(\lambda x) \, _2F_1\left (1,\frac{n+1}{2};\frac{n+3}{2};\coth ^2(\lambda x)\right )}{a \lambda n+a \lambda }\right ) \exp \left (\int _1^x\frac{s \coth ^k\left (\frac{\beta \left (-b \, _2F_1\left (1,\frac{n+1}{2};\frac{n+3}{2};\coth ^2(\lambda x)\right ) \coth ^{n+1}(\lambda x)+a \lambda (n+1) y+b \coth ^{n+1}(\lambda K[1]) \, _2F_1\left (1,\frac{n+1}{2};\frac{n+3}{2};\coth ^2(\lambda K[1])\right )\right )}{a \lambda (n+1)}\right )+c \coth ^m(\mu K[1])}{a}dK[1]\right )\right \}\right \}$

Maple

$w \left ( x,y \right ) ={\it \_F1} \left ( -\int \!{\frac{b \left ({\rm coth} \left (\lambda \,x\right ) \right ) ^{n}}{a}}\,{\rm d}x+y \right ){{\rm e}^{\int ^{x}\!{\frac{1}{a} \left ( c \left ({\rm coth} \left (\mu \,{\it \_b}\right ) \right ) ^{m}+s \left ( -{\rm coth} \left (\beta \, \left ( -\int \!{\frac{b \left ({\rm coth} \left ({\it \_b}\,\lambda \right ) \right ) ^{n}}{a}}\,{\rm d}{\it \_b}+\int \!{\frac{b \left ({\rm coth} \left (\lambda \,x\right ) \right ) ^{n}}{a}}\,{\rm d}x-y \right ) \right ) \right ) ^{k} \right ) }{d{\it \_b}}}}$

________________________________________________________________________________________

##### 6.4.11.5 [1096] Problem 5

problem number 1096

Problem Chapter 4.4.4.5, from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $a w_x + b \coth ^n(\lambda y) w_y = (c \coth ^m(\mu x)+s \coth ^k(\beta y)) w$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (\frac{\coth ^{1-n}(\lambda y) \, _2F_1\left (1,\frac{1}{2}-\frac{n}{2};\frac{3}{2}-\frac{n}{2};\coth ^2(\lambda y)\right )}{\lambda -\lambda n}-\frac{b x}{a}\right ) \exp \left (\int _1^y\frac{\left (s \coth ^k(\beta K[1])+c \coth ^m\left (\frac{-a \mu \, _2F_1\left (1,\frac{1}{2}-\frac{n}{2};\frac{3}{2}-\frac{n}{2};\coth ^2(\lambda y)\right ) \coth ^{1-n}(\lambda y)+b \lambda \mu x-b \lambda \mu n x+a \mu \coth ^{1-n}(\lambda K[1]) \, _2F_1\left (1,\frac{1}{2}-\frac{n}{2};\frac{3}{2}-\frac{n}{2};\coth ^2(\lambda K[1])\right )}{b \lambda -b \lambda n}\right )\right ) \coth ^{-n}(\lambda K[1])}{b}dK[1]\right )\right \}\right \}$

Maple

$w \left ( x,y \right ) ={\it \_F1} \left ( -{\frac{a\int \! \left ({\rm coth} \left (y\lambda \right ) \right ) ^{-n}\,{\rm d}y}{b}}+x \right ){{\rm e}^{\int ^{y}\!{\frac{ \left ({\rm coth} \left ({\it \_b}\,\lambda \right ) \right ) ^{-n}}{b} \left ( c \left ( -{\rm coth} \left (-\mu \,\int \!{\frac{ \left ({\rm coth} \left ({\it \_b}\,\lambda \right ) \right ) ^{-n}a}{b}}\,{\rm d}{\it \_b}-\mu \, \left ( -{\frac{a\int \! \left ({\rm coth} \left (y\lambda \right ) \right ) ^{-n}\,{\rm d}y}{b}}+x \right ) \right ) \right ) ^{m}+s \left ({\rm coth} \left (\beta \,{\it \_b}\right ) \right ) ^{k} \right ) }{d{\it \_b}}}}$

________________________________________________________________________________________